Research on Self-Regulated Learning in Mathematics Learning (1980-2023): A Bibliometric Review - Marchy, Febrinna; Elmawati, Elmawati; Samosir, Christina Monika; Muhammad, Ilham (Universitas Islam Sultan Agung, 2023)
Self Regulated Learning (SRL) is the ability of individuals to effectively use various strategies in achieve their learning goals. The purpose of this study is to capture the research landscape related to Self-Regulation Student learning at the secondary school level from 1980 to 2023. The method used in this study is a descriptive bibliometric analysis method, it is aimed at analyzing scientific literature, focusing on the measurement and description of patterns in bibliographic data. The Scopus database is used as the research data. The results showed that a rapid increase in the number of publications occurred from 2014 to 2015 and from 2017 to 2018. Publications in 2006 were cited more than any other year. The United States of America is the most influential country in this field. Publications in journals related to self-regulated research The most learning is at the Q1 level. The focus of research related to this field is divided into three parts, namely, 1) development, practice, and tasks; 2) strategy, mathematics achievements, and reasoning; 3) environment and understanding. The new theme in this research is self efficacy, attitude, environment, age and reasoning.